Natural substance rutin versus standard drug atorvastatin in a treatment of metabolic syndrome-like condition - Dominika Micháliková; Barbara Tyukos Kaprinay; Boris Lipták; Karol Švík; Lukáš Slovák; Ružena Sotníková; Vladimír Knezl; Zdenka Gaspárová (Elsevier, 2019)
Background: Metabolic syndrome is a cluster of metabolic risk factors. The clear causes of its development are not known yet and there is no comprehensive treatment of this disease. There is a trend to use natural substances in the treatment of various diseases, but their effects need to be well explored. We decided to test effect of rutin compared to the effect of the standard drug atorvastatin. Methods: As a model of metabolic syndrome we used males of hypertriacylglycerolemic rats in combination with high-fat-high-fructose diet. Rutin (100 mg/kg) and atorvastatin (50 mg/kg) were administered orally daily for 5 weeks. Results: We determined biochemical parameters from blood: HDL-cholesterol, LDL-cholesterol, total cholesterol, triacylglycerols. Relaxation and contraction response of aorta was measured to determine vessel dysfunctions and possible predisposition to cardiovascular disease. The negative influence on cognitive functions could be associated with the development of metabolic cognitive syndrome. Therefore we aimed to monitor spatial memory by Morris water maze test. Both rutin and atorvastatin had a tendency to decrease levels of serum triacylglycerols, but only atorvastatin significantly reduced levels od LDL-cholesterol and increased HDL-cholesterol levels. Both compounds significantly reduced the phenylephrine-induced contractile response of the aorta and improved the relaxation response. Further, treated animals learned better compared to untreated rats in the Morris water maze. Conclusion: Based on our results we can assume that atorvastatin and rutin had positive effect on spatial memory and vessel reactivity. Atorvastatin optimized lipid profile of blood serum. Keywords: Metabolic syndrome, Rutin, Atorvastatin, Dyslipidemia, Aorta, Spatial memory